Pandemic potential of the Nipah virus and public health strategies adopted during outbreaks: Lessons from Kerala, India. - Thekkumkara Surendran Anish; Reghukumar Aravind; Chandni Radhakrishnan; Nivedita Gupta; Pragya D Yadav; Jerin Jose Cherian; Rima Sahay; Shubin Chenayil; Anoop Kumar A S; Anitha Puduvail Moorkoth; Ashadevi; Velichapat Ramakrishnan Lathika; et al. (PLOS Global Public Health)
Kerala, a south Indian state witnessed several outbreaks of Nipah encephalitis since 2018, a zoonotic viral disease with significant pandemic potential. This review highlights the relevance of surveillance and health system preparedness, infection control, early diagnosis and treatment with broad-spectrum antivirals, environmental conservation, and community engagement in mitigating Nipah outbreaks. Additionally, it emphasises the importance of developing new biologicals and anti-viral drugs to combat the disease. The article discusses the available evidence on the spillover mechanisms, genetic attributes of the circulating virus, ecological factors, risk of hospital-based superspreading, treatment outcomes and successful strategies employed in Kerala in response to the recurrent Nipah outbreaks.